Untimely illness: When diagnosis does not match age‐related expectations. (9th February 2018) - Kirkpatrick, Susan; Locock, Louise; Farre, Albert; Ryan, Sara; Salisbury, Helen; McDonagh, Janet E.
Abstract: Background: We explore the concept of "untimely diagnosis, " where the onset of a long‐term condition occurs at a life stage which does not conform to traditional expectations, focusing on two conditions (asthma and arthritis) typically associated with a particular life stage (childhood and older adulthood, respectively). Previous literature has focused on the meaning of chronic illness in terms of life history, and the biographical lens has been used in various ways to make sense of the experience. Less attention has been paid to the condition onset when it seems dissonant with chronological age. Methods: Secondary analysis of two qualitative data sets (total 58 interviews) exploring the experiences of people with adult‐onset asthma and young people diagnosed with arthritis. Data from the original interview transcripts relating to diagnosis and symptom recognition were re‐analysed using a "candidacy" framework to examine how age and diagnosis intersect. Results: People did not always assert their candidacy for either condition because of pre‐conceived expectations around age. Similarly, health professionals sometimes failed to recognize patients' candidacy, instead pursuing "age‐plausible" possibilities. In some cases, participants were proactive in suggesting a diagnosis to the health professional where diagnosis was delayed. Conclusion: The diagnosis of adult‐onset asthma, and arthritis in young people, may be regarded as "untimely." We suggest that being diagnosed with what is perceived to be a "childhood" condition in adulthood, or "an older person's" condition in childhood, may be viewed as a "biographical paradox" and an "untimely breach" to the expected order.